Pengembangan Modul “CIKINI” dan Pelatihan Kader Untuk Mewujudkan Desa Ramah Lansia di Cikawao - Yoko Jimmy Panjaitan; Alfi Fauzia Hakim; Linda Widyastuti; Ira Hasianna Rambe (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
Cikawao Village, located in Pacet District, Bandung Regency, is a rural area characterized by strong social cohesion, communal values, and local wisdom. The elderly population constitutes a significant proportion of the community and requires special attention in efforts to promote sustainable community development. This community service program aimed to support the development of an Age-Friendly Village through a psychosocial approach that emphasizes active participation, intergenerational collaboration, and community empowerment. The program was carried out through three main activities: (1) participatory data collection and health screening for older adults, (2) training of age-friendly cadres focusing on empathic communication and the psychology of aging, and (3) the development of the CIKINI (Carita Jeung Aki Nini) module as a community-based tool for psychosocial education and social engagement. The program involved collaboration among lecturers, students, village officials, community organizations, and local leaders. The results demonstrated improved knowledge and skills of participants, increased community awareness regarding the role of older adults, and a collective commitment through the declaration of Cikawao as an Age-Friendly Village. This initiative is expected to serve as a sustainable model for promoting elderly well-being through psychosocial empowerment and community-based participation.